2006
DOI: 10.1152/ajplung.00114.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of 12-lipoxygenase in hypoxia-induced rat pulmonary artery smooth muscle cell proliferation

Abstract: The 12-lipoxygenase (12-LO) pathway of arachidonic acid metabolism stimulates cell growth and metastasis of various cancer cells and the 12-LO metabolite, 12(S)-hydroxyeicosatetraenoic acid [12(S)-HETE], enhances proliferation of aortic smooth muscle cells (SMCs). However, pulmonary vascular effects of 12-LO have not been previously studied. We sought evidence for a role of 12-LO and 12(S)-HETE in the development of hypoxia-induced pulmonary hypertension. We found that 12-LO gene and protein expression is elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 94 publications
(49 reference statements)
4
68
0
Order By: Relevance
“…Phenamil (15 or 30 mg/kg of body weight/day) was administered continuously for 21 days at an infusion rate of 1 ml/h. The rats were subjected to hypobaric hypoxia (10.5% oxygen) or normoxia (room air) for 21 days as described previously (34).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenamil (15 or 30 mg/kg of body weight/day) was administered continuously for 21 days at an infusion rate of 1 ml/h. The rats were subjected to hypobaric hypoxia (10.5% oxygen) or normoxia (room air) for 21 days as described previously (34).…”
Section: Methodsmentioning
confidence: 99%
“…The right ventricular peak pressure (RVPP) was measured by inserting a 26-gauge needle with 12 in. of P-50 tubing connected to a pressure transducer into the right ventricle (RV) as described previously (34). Continuous measurement of RV pressure was recorded on a polygraph, and RVPP was measured as the highest pressure recording over a 1-to 3-min period during which pressure recordings remained stable.…”
Section: Methodsmentioning
confidence: 99%
“…While hypoxia-induced remodeling is associated with medial hypertrophy, direct stimulation of SMC proliferation by hypoxia remains somewhat controversial (37). Although there are reports of hypoxia driven smooth muscle cell proliferation (38,39), several in vitro studies have shown that hypoxia does not directly increase SMC proliferation (40)(41)(42) or may actually decrease proliferation (43,44). However, fibroblasts that are less differentiated than the other two main vascular cell types, have a greater proliferative response to hypoxia (44)(45)(46).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%
“…The 12-lipoxygenase (LO) pathway of arachidonic acid metabolism has been linked to cell growth and the pathology of hypertension (Preston et al, 2006). Ang II is a potent positive regulator of 12-LO expression and proliferation in porcine and human vascular smooth muscle cells (VSMCs) (Natarajan et al, 1993;Kim et al, 1995).…”
Section: Introductionmentioning
confidence: 99%